Prevalence and associations of anisometropia with spherical ametropia, cylindrical power, age, and sex, based on 134,603 refractive surgery candidates - Mona Deuchert; Andreas Frings; Vasyl Druchkiv; Jakob Schweighofer; Sajjad Muhammad; Stephan Linke; Toam Katz (PLoS ONE, 2025)
Purpose To examine the prevalence and associations of anisometropia with spherical ametropia, cylindrical power, age, and sex. Methods Anisometropia was analyzed for subjective refraction. In total, 134,603 refractive surgery candidates were included in the period from 2010 to 2020 at the CARE Vision Refractive Centers in Germany. Our study was approved by the local ethics committee at the University in Duesseldorf (approval date: February 9, 2021) and conducted according to the tenets of the Declaration of Helsinki and Good Clinical Practices Guidelines. The treatment contract included explicit patient consent to use medical data for scientific purposes. Correlations between anisometropia and explanatory variables were analyzed using the chi-squared test (χ2 test), nonparametric Kruskal–Wallis or Mann–Whitney U-tests, and binomial logistic regression. Power vector analysis was applied for further analysis of cylindrical power. Results The median level of anisometropia (Asubj) in the whole population was 0.38 D. The prevalence of Asubj was 17.9%. In hyperopes, all explanatory variables (spherical ametropia, cylindrical power, age, sex) were independently associated with anisometropia. Asubj decreased with increasing cylindrical ametropia: an increase in cylindrical power by 7.8 D reduced the chance of observing anisometropia by half. It was also associated with male sex. Asubj decreased by half with a 16.7 D increase in spherical power and an increase in age by 22.7 years. In myopes, cylindrical power was most strongly associated with anisometropia: an increase in (negative) cylindrical power by 2.15 D doubled the chances of observing anisometropia in myopes. In addition, advancing age (double chance with an increase of 38.3 years), increasing spherical power (double chance with an increase of 8.15 D), and female sex correlated positively with increasing anisometropia in myopes. Conclusions This retrospective analysis gives evidence for the independent association between anisometropia and spherical power, cylindrical power, age, and sex in myopic refractive surgery candidates. The relation of anisometropia with age was positive in myopes but negative in hyperopes. The analysis of sex revealed a positive relation of female sex and anisometropia in myopes and furthermore revealed a positive relation of male sex and anisometropia in hyperopes. Further clinical research into the underlying mechanisms behind our findings is indicated.